Fatores de risco da transmissão de zoonoses por costumes da população de Ilha Solteira, Brasil - Sánchez-Ortiz, Iván A.; Leite, Maurício A. [UNESP] (My University, 2011)
Objective Determining conditions regarding possible zoonosis transmission risk based on Ilha Solteira-São Paulo citizens' habits aimed at establishing concrete recommendations for the corresponding local authorities to reduce some risk factors. Methods100 focalized interviews were held on Ilha Solteira's urban perimeter during April 2008. The people interviewed were adults who lived or worked in houses in the study area. Results This research found a significant number of cat and/or dog owners who allowed their pets to stay in internal areas of their houses. They did not define a specific place for animals to defecate and/or urinate or did not arrange appropriate final disposal of such waste. Conclusion Local authorities must make greater efforts at educating Ilha Solteira pets' owners and providing them with information and encouraging greater citizen commitment and awareness to improve habits related to caring for pets/animal sand reducing zoonosis transmission risk factors.
Zoonosis transmission risk factors according to population habits Inilha Solteira city, Brazil
Keywords: Pets; Public health; Zoonoses (source: MeSH, NLM); adult; animal; animal disease; Brazil; cat; disease transmission; dog; habit; human; leptospirosis; pet animal; questionnaire; risk factor; sanitation; toxoplasmosis; urban population; zoonosis; Adult; Animals; Cats; Dogs; Habits; Humans; Leptospirosis; Questionnaires; Risk Factors; Sanitation; Toxoplasmosis; Toxoplasmosis, Animal; Urban Population; Zoonoses